Predlog funkcijskih značilnosti faze zasnove v konstrukcijskem postopku - Golob, Borut (Strojniški vestnik, 2003)
Product design is an iterative, complex and decision-making process, performed by designers. It usually starts with recognition and specifying requirements and demands, followed by searching for an optimum solution, for the required tasks. After an evaluation of the concept solutions and the selection of promising solutions comes detailing with the layout definition, and a description of the product. Conceptual design has been recognised as an important part of the design process, but receives weak computer support due to complex and informal data that is hard to retreive, store and maintain with computers. Besides geometrical data, it is important to capture, represent and process the function and the behaviour of a product. The presented approach is future-based modelling of product semantics and function that takes place already in the conceptual design phase. The features are taken the information carriers that allow modelling of the relationship between the requirements of a product, its functional description and physical solutions. These features will also bring this information to the downstream applications.
Keywords: značilnosti funkcijske; zasnova konstrukcijska; konstruiranje metodično; konstruiranje; načrtovanje; modeliranje; izdelki